2023
DOI: 10.3390/plants12091779
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IAA in Regulating Root Architecture of Sweetpotato (Ipomoea batatas [L.] Lam) in Response to Potassium Deficiency Stress

Abstract: Plants can adapt to the spatial heterogeneity of soil nutrients by changing the morphology and architecture of the root system. Here, we explored the role of auxin in the response of sweetpotato roots to potassium (K+) deficiency stress. Two sweetpotato cultivars, Xushu 32 (low-K-tolerant) and Ningzishu 1 (low-K-sensitive), were cultured in low K+ (0.1 mmol L−1, LK) and normal K+ (10 mmol L−1, CK) nutrient solutions. Compared with CK, LK reduced the dry mass, K+ content, and K+ accumulation in the two cultivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Although crown roots, as post-embryonic roots, play a crucial role in nutrient uptake during the later stages of maize growth, their importance during the seedling stage is relatively minor [ 40 ]. In studies on different low-K-tolerant sweet potato varieties, it was found that IAA can modulate root plasticity, promoting K + uptake and dry matter accumulation in sweet potatoes under low-K + stress [ 23 ]. Similarly, we also observed that exogenous NAA can enhance K + absorption and dry matter accumulation in maize seedlings under K-deficiency, with a more pronounced increase in K + concentration in the D937 root system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although crown roots, as post-embryonic roots, play a crucial role in nutrient uptake during the later stages of maize growth, their importance during the seedling stage is relatively minor [ 40 ]. In studies on different low-K-tolerant sweet potato varieties, it was found that IAA can modulate root plasticity, promoting K + uptake and dry matter accumulation in sweet potatoes under low-K + stress [ 23 ]. Similarly, we also observed that exogenous NAA can enhance K + absorption and dry matter accumulation in maize seedlings under K-deficiency, with a more pronounced increase in K + concentration in the D937 root system.…”
Section: Discussionmentioning
confidence: 99%
“…However, the K-tolerance phenotype disappears in arf2 -mutant plants upon knockout of the HAK5 gene [ 21 , 22 ]. Furthermore, in sweet potatoes, genes related to auxin ( IbPIN1 , IbPIN3 , IbAUX1 , IbIAA4 , and IbIAA8 ) were found to participate in regulating sweet potato lateral root formation and root architecture changes under K-deficiency treatment, promoting K uptake and biomass formation [ 23 ]. In our preliminary research, we found that, under K-deficiency, compared to those in the K-sensitive inbred line D937, the root length, root volume, and root surface area of the K-tolerant maize inbred line 90-21-3 significantly increased, accompanied by a significant increase in indole-3-acetic acid (IAA) content [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of sweet potato root tubers is caused by auxin-induced activation of the root cambium and xylem cell proliferation, thus promoting the enlargement of the root tubers [ 5 ]. Moreover, IAA participates in the formation of lateral roots and the change in root architecture of sweet potato under the low K + stress [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…proliferation, thus promoting the enlargement of the root tubers [5]. Moreover, IAA participates in the formation of lateral roots and the change in root architecture of sweet potato under the low K + stress [6].…”
Section: Introductionmentioning
confidence: 99%
“…During the early stage of storage root development, the endogenous IAA content and SRD1 transcript level increased concomitantly, SRD1 -overexpressing transgenic sweet potato plants cultured in vitro produced thicker and shorter fibrous roots than wild-type plants, suggesting an involvement of SRD1 during the early stage of the auxin-dependent development of the storage root [ 14 ]. The early accumulation of IAA in the rooting zone stimulated the formation of ARs in cuttings [ 13 , 15 ]. Many studies suggest that the genes related to phytohormone, IAA, jasmonic acid (JA), and lignin biosynthesis are widely used for clonal plant propagation in sweet potato SRs [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%